منهج تعليم اللغة العربية لمدرسة المعلمين والمعلمات المتوسطة الإسلامية بمعهد سونان دراجات لامونجان - Muhammad Tarekh Aziz (UIN Fatmawati Sukarno Bengkulu, 2022)
Curriculum is an important instrument for success in education, because without an appropriate curriculum it will be difficult to achieve educational goals. Many students have difficulty in learning foreign languages such as learning Arabic, of all of them, Mu'allimin Mu'allimat boarding school uses Different curriculum, after researchers conducted interviews with teachers who teach there, the real aim of students is clever in writing, reading Arabic writing, and memorizing Arabic rules of learning. As for the other characteristics in Arabic language learning materials there using the books of Turkish.Researchers here use a qualitative approach and analytic descriptive case studies which reveal the characteristics and strengths of schools that are different from the others, while the data collection methods used by researchers are observation, interviews and documents. In the validity of the data the researcher uses 4 steps: checking the accuracy of the data, conclusions of the data, usefulness of the data and confirming the data.As for the results of this study, the Arabic language teaching curriculum at the school is 1) The purpose of the school is that students can be clever in writing, reading and memorizing Arabic language rules. 2) the material used in this school is Arabic language learning based on Islamic boarding school curriculum. 3) the method used is the audiolingual method, the qoidah and tarjamah or bandongan method, the memorization method, the singing method, the imla method 'and the reading method. The memorization method and the bandongan method are characteristics of the pesantren curriculum. 4) The evaluation used is using the pesantren curriculum evaluation with 3 methods, namely written test, Arabic book reading test, and memorization test. But in this school there are additional special oral tests on Nahwu subjects.